STRUCTURED OPERATIONAL READINESS FOR PROCESS SAFETY MANAGEMENT - MOHAMMED JAMIL MUSTAFA MALOSOK, OMAR (IRC, 2017)
Operational Readiness is one of the twenty Risk Based Process Safety (RBPS) elements issued by the Centre for Chemical Process safety (CCPS). Nevertheless, unlike some of the elements in the RBPS approach, there is little explanations, guidance and development on the way to comply with this element and how to implement it efficiently and accurately in the process industry. since the issues with the operational readiness of processes started to emerge. An Operational Readiness model is introduced that is based on the CCPS RBPS standard to produce a structured model that is easier to understand and apply by operators, engineers or process readiness review owner. A case study based on an industrial process is performed to verify the effectiveness and to ensure the RBPS standard applies. This model has the potential to provide users with useful tool and instructions to better manage the operational readiness element and also to reduce the time consumed when it is implemented